EVALUASI MANAJEMEN ASET DALAM MENGOPTIMALKAN PENGELOLAAN ASET TETAP DAERAH KOTA SEMARANG - Tri Rinawati; Purwati Purwati; Citra Rizkiana (POLITEKNIK LP3I JAKARTA, 2022)
The purpose of this study was to determine the management of BMD in Semarang City and to determine efforts to optimize the management of BMD in Semarang City. This type of research is qualitative or case study. The data collection method is carried out in natural settings (natural conditions), primary data sources, and data collection techniques are mostly on observation, interviews, and documentation. Qualitative data processing methods can be done through three stages, namely data processing, data presentation, and drawing conclusions. There are four data validity criteria, namely validity, portability, robustness and confirmability. In verifying the data, the researcher used the data validation method, namely triangulation. The results of the study concluded that the Semarang City Regional Asset management mechanism was basically in accordance with Permendagri 17 of 2021 concerning Systematic Technical Guidelines for Bookkeeping, Inventorying and Reporting of BMD. However, in practice the implementation of this regulation has not been maximized, this is due to several obstacles in its implementation. One way that must be taken to achieve accountability and transparency in the management of BMD is by publication, namely to find out information about regional assets/goods using the internet. Information about regional assets/goods owned by a government that is given to the public will increase public confidence in the control of BMD. As long as the assets are in their useful life, their use must be optimized using a rental mechanism, namely the use of regional property by other parties for a certain period of time by receiving money in return; then the build-to-hand-over (BGS) and the build-to-use (BSG) mechanisms.Keywords: Asset Management, Regional Asset Management